Interview with Steven Livingston on Information Systems and Development - World Bank (2012)
An Interview with Steven Livingston, Professor of Media and Public Affairs and International Affairs. His research and teaching focus on media, information technology, national security and global politics. Dr. Livingston’s most recent publications include, When the Press Fails: Political Power and the News Media from Iraq to Katrina (2007), co-authored with W. Lance Bennett and Regina Lawrence) and Africa’s Evolving Infosystems: A Pathway to Security and Stability (2010), assessing the effects of the rapid growth of ICT on governance in Africa.